HYGIENIC DEFINITIONS OF WORKING CONDITIONS OF HEMATOLOGISTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This in the article hematologists labor conditions hygienic in terms of modern scientific literature based on analysis Analysis to the results according to , laboratory employees between biological danger factors advantage to do detected , needle injuries in 25–40% of cases meeting , blood through contagious infections danger height record Also , chemical substances effect in 20–25% of cases observation and ergonomic problems wide prevalence was determined . In the article labor hygiene modern approach — occupational hygiene program system based on risks detection , monitoring and control to do mechanism illuminated. Obtained results hematologists labor conditions improve and professional risks reduce according to scientific based conclusions to release opportunity gives .